HUBUNGAN KONSUMSI BUAH DAN SAYUR DENGAN KEJADIAN GEJALA DEPRESI PADA MAHASISWA S1 GIZI - Zuhrah, Poppy; Ismawati, Rita (Departement of Nutrition, Faculty of Public Health, Hasanuddin University, Makassar, 2023)
Introduction : Consuming fruits and vegetables regularly in the right portions has a major impact on the metabolism of the body and is associated with various health problems, one of which is related to symptoms of depression. For this reason, consumption of fruits and vegetables in sufficient portions needs to be done by each individual. Methods: This is a type of analytical observational research using a cross-sectional method. Respondents in this study were students of the Bachelor of Nutrition study program at Surabaya State University, totaling 79 female respondents. Data were collected using the CES-D and SQ-FFQ questionnaires via a goggle form. The chi-square test was used for data analysis. Results: In this study, the majority of respondents had less fruit and vegetable consumption, namely 50 people (63.3%) consumed fruit and 47 people (59.5%) consumed vegetables. There were 45 students (57%) had depressive symptoms, whereas 34 (43%) did not. The results of the analysis showed that fruit consumption and the incidence of depressive symptoms had a p-value <0.001, whereas the consumption of vegetables and the incidence of depressive symptoms had a p-value = 0.01. Conclusion: The results show a relationship between fruit consumption and the incidence of depressive symptoms among undergraduate students of the Nutrition Study Program at Surabaya State University, and a relationship between vegetable consumption and the incidence of depressive symptoms in students of the Nutrition Undergraduate Study Program at Surabaya State University. Attention needs to be paid to fruit and vegetable consumption behaviors in students and their mental health.